KONTRIBUSI PANJANG TUNGKAI, KEKUATAN TUNGKAI DAN KESEIMBANGAN DENGAN KEMAMPUAN JAUHNYA TENDANGAN DALAM PERMAINAN SEPAKBOLA PADA MAHASISWA STKIP PARIS BARANTAI KOTABARU - Arham Syahban (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2015)
Of the research is descriptive research using a design study "correlation". This study to determine: (1) Is there any contribution limb length with the ability to kick away in the game of football on the student STKIP Paris Barantai?, (2) Is there any contribution leg strength with the ability to kick away in the game of football on the student STKIP Paris Barantai?, (3) Is there a balance contributions with the ability to kick away in the game of football on the student STKIP Paris Barantai?, and (4) Is there any contribution leg length, leg strength and balance with the ability to kick away in the game of football on the student STKIP Paris Barantai? Pupils student population is STKIP Paris Barantai Kotabaru. The sample used was a student STKIP Paris Barantai Kotabaru many as 40 people. Sampling technique is by random selection by lottery (Simple Random Sampling). Data analysis technique used is descriptive analysis, analysis of Pearson product moment correlation coefficient (r), regression analysis and analysis of multiple correlation (R) by SPSS 22 at the 0.05 significance level Î±. The results showed that; (1) There is a long contribution to the ability away leg kicks in the game of football on the student STKIP Paris Barantai, with a value (r) of 0.760 (pvalue <Î± 0,05); (2) There is a contribution leg strength with the ability to kick away in the game of football on the student STKIP Paris Barantai, with a value (r) of 0.631 (pvalue <Î± 0,05); (3) There is contributing the balance with the ability to kick away in the game of football on the student STKIP Paris Barantai, with a value (r) of 0.446 (pvalue <Î± 0,05); (4) There is a contribution leg length, leg strength and balance with the ability to kick away in the game of football on the student STKIP Paris Barantai, the R value of 0.771 (pvalue <Î± 0,05); and value Fhitung 17.630.